2020
DOI: 10.1113/jp279577
|View full text |Cite
|
Sign up to set email alerts
|

Regular moderate exercise alleviates gastric oxidative damage in rats via the contribution of oxytocin receptors

Abstract: Key points A moderate level of exercise has beneficial effects for the prevention of gastric ulcers. Although regular aerobic exercise was shown to elevate serum oxytocin levels and exogenously administered oxytocin exerts an anti‐ulcer activity, the role of endogenous oxytocin in the gastroprotective effects of exercise has not yet been elucidated. We showed that increased anxiety and oxidative gastric damage induced by gastric ulcers were reversed in pre‐exercised rats, while reduced hypothalamic oxytocin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Histopathological evaluation was made semi-quantitatively with a maximum score of 12 for gastric tissues (0, none; 1, mild; 2, moderate; 3, severe). Histopathological criteria for the evaluation of gastric tissues were desquamation of surface epithelium, hemorrhage, focal necrosis and mucosal congestion, degeneration of glandular cells, and inflammatory cell infiltration (Arabacı Tamer et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological evaluation was made semi-quantitatively with a maximum score of 12 for gastric tissues (0, none; 1, mild; 2, moderate; 3, severe). Histopathological criteria for the evaluation of gastric tissues were desquamation of surface epithelium, hemorrhage, focal necrosis and mucosal congestion, degeneration of glandular cells, and inflammatory cell infiltration (Arabacı Tamer et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…PUD results from an imbalance between the protective (e.g., mucus, bicarbonate, prostaglandins, antioxidant system and cell proliferation) and destructive (e.g., gastric acid, pepsin, Helicobacter pylori , stress, nonsteroidal anti-inflammatory drugs (NSAIDs) and alcohol) factors (Laine et al 2008 ; Sverdén et al 2019 ), while impaired gastric blood flow, oxidant damage, apoptosis, production of reactive oxygen metabolites and pro-inflammatory cytokines (e.g., tumor necrosis factor (TNF)-α, interleukin (IL)-6 and IL-1β) along with alterations in the expressions of nuclear factor kappa B (NF-κB) and prostaglandins (PGI2 and PGE2) aggravate gastric injury (Arabaci Tamer et al 2021 ; Kolgazi et al 2017 ; Tamer et al 2022 ). Experimental gastric ulcer induced by acetic acid, which affects the entire gastric mucosa and submucosa and penetrates the muscularis mucosa, mimics the morphological and clinical findings observed in peptic ulcer patients (Arabacı Tamer et al 2020 ; Okabe and Magase 2005 ), and therefore it is widely used as a chronic gastric ulcer model to investigate putative anti-ulcer alternative medications (Oyetayo et al 2022 ; Wang et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vehicle group: Rats received an intraperitoneal injection of a mixture containing corn oil and DMSO (Medchemexpress/USA) 30 minutes before ischemia induction. Subsequently, they underwent 30 minutes of bilateral renal ischemia and 2 hours of reperfusion [21]. The vehicle group was established to mitigate any impact of DMSO and corn oil on the outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…The intestine was retracted, and the abdomen and both renal pedicles were exposed through a midline laparotomy incision. For the bilateral ischemia model, the renal pedicles were isolated by placing non-trauma microvascular clamps around the renal arteries and veins [21]. After a few minutes, the kidney's color changed from red to dark purple, accompanied by pale stains on the kidney surface, indicating blood flow blockage.…”
Section: Experimental Study Modelmentioning
confidence: 99%
“…Lastly, some evidence suggested that exercise also modulates changes in OXT levels and OXT expression. In rats with gastric injury, regular, moderate-intensity exercise upregulates oxytocin activity and alleviates gastric injury [ 154 ]. Similar results were obtained in a mouse model of breast cancer [ 155 ].…”
Section: Introductionmentioning
confidence: 99%